1987
DOI: 10.1264/microbes1986.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Annual Fluctuations of Phytoplankton and Bacterial Communities in Maizuru Bay and their Interrelationship

Abstract: The annual changes in bacterial community were studied as related to those of phytoplankton in Maizuru Bay, Japan from May 1985 to April 1986 Five phytoplankton blooms were observed through the year Dominant algal species for three blooms were diatoms, Cerataulina pelagica, Asterionella japonica and Leptocylindrus danicus, and for the other two, dinoflagellate Prorocentrum micans and Raphidophycean Chattonella marina, respectively. The analysis of the bacterial community revealed that in these blooming periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Riquelme et al (1987) investigated bacterial community structure before and after some algal blooms and observed that high densities of the Pseudomonas sp. 022 developed just before the alga Asterionella glacialis (= japonica) bloomed.…”
Section: Stimulative Effect Of Naturally Occurring Bacteria On the Grmentioning
confidence: 99%
“…Riquelme et al (1987) investigated bacterial community structure before and after some algal blooms and observed that high densities of the Pseudomonas sp. 022 developed just before the alga Asterionella glacialis (= japonica) bloomed.…”
Section: Stimulative Effect Of Naturally Occurring Bacteria On the Grmentioning
confidence: 99%
“…It is generally thought that the algae and bacteria maintain symbiotic relations. Previous work has shown that the presence of bacteria may aid algal productivity (Andersen, ; Fukami et al, ; Riquelme et al, ; Suminto and Hirayama ). The stimulative effect of bacteria on algal growth has been described as being associated with bacteria mineralizing carbon (Ask et al, ; Muñoz and Guieysse, ), as well as cycling nutrients (Bloesch et al, ; Zhao et al, ) and generating vitamins (Grant et al, ) and other growth promoting regulators.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the cells in exponential growth produced less exudates and detritus than those cultured at 18-L and 400-L. On the other hand, secondary metabolites such as amino acids, carbohydrates, and vitamins required for bacterial growth are generally produced during the stationary phase. The highest density of bacterioplankton occurs after the maximum production of phytoplankton [16] [17], and under in vitro conditions the maximum abundance of bacteria occurs after the maximum production of chlorophyll a [18]. Our results therefore indicate that as the culture volume increases, the abundance of bacteria increases; hence, bacteria can be introduced into systems used for aquaculture production of crustacean and mollusc larvae when C. muelleri is used as food.…”
Section: Microalgal Growthmentioning
confidence: 79%